PTH-055 ABO Blood Group-Specific Immunoglobulins in Crohn's Disease. (17th August 2016) - Ting, CW-T; Hussain, S; Wurie, S; O'Connell, N; Higgins, R; Briggs, D; Krishnan, N; Arasaradnam, R; Daga, S
Abstract : Introduction: The pathogenesis of Crohn's disease (CD) is complex and believed to be interplayed by genetic susceptibility, enteric microflora and tissue injury mediated by abnormal immune response. Several studies have described the association between ABO blood group, enteric microflora composition and predisposition to gastrointestinal (GI) infections. The mucosal layer of the GI tract forms the first layer of immune defenses with mucus abundant in secretory immunoglobulins, and studies have shown that non-O blood group and FUT2-determined ABO antigen non-secretor were linked to more severe CD. It was suggested that ABO antibodies are induced via an enteric route by cross-reactivity from microflora-derived molecules . However, little is known about the role of ABO antibodies in the context of CD. Therefore we assessed whether blood group-specific antibodies are implicated in CD pathogenesis. Methods: We compared the immunoglobulin class profile of blood group-specific antibodies in blood group A, B and O individuals. Plasma samples were collected from CD cohort (n = 45, recruited from the FaMIsHED study) with age- and gender-matched healthy donors (n = 89 data from service development study). Medications of CD cohort include none (n = 15), 5 ASA (n = 21), immunosuppressant (n = 12) and biologics (n = 10). A1rr and Brr cells were used, anti-A1 and anti-B IgG, IgA and IgM levels were measured by Relative Median Fluorescence using flow cytometry. Mann-Whitney U test was used to assess statistical significance of different antibody levels between CD and healthy cohorts. Results: Blood group O CD patients (n = 20) have significantly lower anti-A1 IgG, IgA and IgM compared to the healthy blood group O cohort with p value of 0.0001, 0.0009 and <0.0001 respectively; but only anti-B IgM was significantly lower (p = 0.005) in the CD patients compared to controls and no significant difference was observed in IgG (p = 0.5197) and IgA (p = 0.626). Blood group A CD patients (n = 19) was found to have lower anti-B IgG response (p = 0.041) and no significant difference was found in anti-B IgA (p = 0.2748) and IgM (p = 0.2012) levels. Blood group B CD patients (n = 6) were found to have lower anti-A1 IgA (p = 0.0131) compared to healthy controls but no significant difference was observed in IgG (p = 0.101) and IgM (p = 0.174). Conclusion: CD patients were found to have lower than baseline ABO antibodies. However, it is not known whether these findings represent the cause or effect of disturbed immune modulations, or their roles in modulating intestinal microflora. Further research into the difference in ABO antibodies class profile in a larger cohort, and comparison of ABO antibodies class profile of CD patients in remission and relapse are required. Disclosure of Interest: None Declared